Szanse życiowe dzieci z różnych kategorii rodzin - Taranowicz, Iwona (Wydawnictwo Naukowe UAM, 1999)
The transformation of political and economic system in Poland also means the change of social system. Other skills and features of personality become important. We are interested in how families socialize their children to life under the new social conditions. In our study we are focused on: 1. additional educational activities, 2. retreats, 3. features of personality which parents prefer, 4. children’s own money. Results of 209 interviews made among families which have children at school age indicate the significant relationship between the socioeconomic status of family and each of issues that we studied. Family socialization strenghtens existing social inequality.
Life’s prospects of children from different kinds of families